2000
DOI: 10.1099/00207713-50-2-665
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of AFLP and rep-PCR genomic fingerprinting with DNA-DNA homology studies: Xanthomonas as a model system.

Abstract: The genus Xanthomonas contains a large number of strains, which have been characterized by a variety of phenotypic and genotypic classification methods. The Xanthomonas collection constitutes one of the largest groups of bacteria that have been characterized phylogenetically by DNA-DNA homology studies and genomic fingerprinting. Presently, a total genomic DNA-DNA homology value of 70 % represents an internationally accepted criterion to define bacterial species levels. However, the complexity of DNA-DNA reass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
249
2
12

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(283 citation statements)
references
References 37 publications
20
249
2
12
Order By: Relevance
“…1), together with data from other studies (Rademaker et al, 2000;Vauterin et al, 1995), suggest that DDH values are continuous, i.e. theoretically, every value between 0 and 100 % could be obtained in DDH experiments.…”
Section: Discussionmentioning
confidence: 99%
“…1), together with data from other studies (Rademaker et al, 2000;Vauterin et al, 1995), suggest that DDH values are continuous, i.e. theoretically, every value between 0 and 100 % could be obtained in DDH experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The mural painting strains were first screened by REP-PCR fingerprinting to group the isolates, since it has been shown that in general REP fingerprinting is in close agreement with DNA-DNA relatedness studies (Nick et al, 1999 ;Rademaker et al, 2000). The 13 isolates showed four REP types that can be subdivided into three major groups at less than 10 % similarity (Pearson coefficient).…”
Section: Notementioning
confidence: 99%
“…AFLP has proven to be useful for identifying bacterial strains at subgeneric level [5,10,11,14,15,17,18,20]. Although the results of AFLP fingerprinting are specific and show high resolution to differentiate bacterial strains at the subgeneric level, it is very clear that the efficacy of this method not only depends on the choice of a suitable restriction enzyme that cleaves the most stable site in the bacterial genome but also depends on application of suitable primer to amplify the unique fragment of bacterial genome which can differentiate one strain from the others.…”
Section: Resultsmentioning
confidence: 99%
“…Rademaker et al [17] compared AFLP, rep-PCR and DNA-DNA homology for the strains of genus Xanthomonas and observed high correlation, suggesting that genomic fingerprinting techniques truly reveal genotypic and phylogenetic relationships of organisms. Gonzalez et al [5] using AFLP distinguished pathogenic and nonpathogenic strains of X. axonopodis pv.…”
Section: Introductionmentioning
confidence: 99%